Enhanced apoptotic activity of Pluronic F127 polymer-encapsulated chlorogenic acid nanoparticles through the PI3K/Akt/mTOR signaling pathway in liver cancer cells and in vivo toxicity studies in zebrafish - Alanazi, Fehaid; Elderdery, Abozer Y.; Alzahrani, Badr; Alzerwi, Nasser A. N.; Althobiti, Maryam Musleh; Rayzah, Musaed; Alanazi, Abdulaziz Suailem; Kuriri, Fahd A.; Idrees, Bandar; Alenazy, Fawaz O.; Alsultan, Afnan; Rayzah, Fares; et al. (De Gruyter, 2023)
In this study, chlorogenic acid nanoparticles encapsulated in Pluronic F127 polymer were synthesized and characterized to determine if they could treat human liver cancer. The nanoparticles were synthesized using standard procedures and characterized using physical and biological techniques such as X-ray diffraction, Fourier transform infrared spectroscopy, UV-Vis, dynamic light scattering, Photoluminescence, scanning electron microscopy, and transmission electron microscopy. The anticancer effects were assessed using MTT analysis, acridine orange/ethidium bromide, reactive oxygen species (ROS), COMET assay, annexinV/FITC, cell cycle analysis, and expression of marker genes against HepG2 cell lines. The results showed significant cytotoxicity, apoptosis induction, and increased ROS production in treated cells compared to control cells. The nanoparticles also activated the apoptotic cascade and regulated the PI3K/AKT/mTOR pathways. The nanocomposites exhibited unique characteristics such as anticancer efficacy in vitro. Further research was conducted using zebrafish to model hematological parameters, liver enzymes, and histopathology to study effectiveness. Green-synthesized Pluronic F127“chlorogenic acid nanoparticles can be considered potential cancer therapy agents.